การศึกษาการดำเนินงานวิชาการในโรงเรียนอาชีวศึกษาเอกชนที่ได้รับรางวัลพระราชทาน ปีการศึกษา 2545 - ศิริชัย จำรัสเลิศลักษณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The purposes of this research were to study state and problems of the operation of academic tasks in Royal Awarded Private Vocational Schools, Academic year B.E. 2545. Populations were the school s administrators, department heads and teachers. The resarch instruments consisted of the semi-structured interview sheets, questionnaire, and documentary study form and data were analyzed by using content analysis, frequency and percentage. Research findings were as follows: Most schools had their academic operations as : 1) curriculum development ; department heads and teacher analyze and prepared courses offered prior to submitted to academic section. Instructional supervision and lesson plan submissions were used as supervisory methods, then they were utilized for instructional development. 2) instruction development ; they emphasized on actual performance, instructional plans were prepared, classroom research were emphasis. Local wisdom were also encouraged for application in teaching. Sufficient budget was provided for instruction. 3) evaluation system ; they used the method of individual differences, formative and summative evaluation. Academic section provided criteria for evaluation. The results of evaluation were reports to students and parents. Data were used for instructional development. 4) student activities ; both academic and personality development were emphasized in planning their activities which were responsible by activity advisor. Student welfare were also provided in most schools. 5) learning resources development ; sufficient amount were provided together with the up-to-date principles. Students were encouraged and they were provided with sufficient and relaxation atmosphere. 6) research, education technology and educational innovation ; department planning and project are prepared with the school s support in form of budget, equipment and tool, training and research result application for actual learning in classroom. Regarding the problems of the operation of academic tasks by most of these schools were such as lack of teacher s understanding and knowledge for curriculum development, insufficient instructional media by teachers, lack of student s interesting and participation in the activities, and finally, inefficient learning source utilization.